Implementasi projek penguatan profil pelajar Pancasila tema kewirausahaan di sekolah dasar - Annisa Nur Fadhilah; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2025)
This research aims to analyze the implementation of the project to strengthen the profile of Pancasila students Entrepreneurship theme at Karangasem 2 State Elementary School starting from the planning, implementation, and evaluation stages. This research approach is qualitative using the case study method. The data sources for this research are the school principal, fourth grade teachers, and fourth grade students. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique uses interactive model analysis techniques. The results of this research indicate that the P5 planning for the Entrepreneurship theme has not been implemented optimally, as shown by Karangasem 2 State Elementary School not developing the capacity of educators in implementing P5 and the team of facilitators and fourth grade educators not creating a flow of P5 activities when implementing P5. In addition, educators do not carry out diagnostic assessments on students before implementing P5. The implementation of P5 Entrepreneurship theme has not been carried out optimally, as shown by Karangasem 2 State Elementary School not yet optimizing the involvement of partners or the community outside the education unit to become learning resources for students. Evaluation and follow-up on P5 of the Entrepreneurship theme is by inviting the school environment to think about ways to optimize the impact and benefits of profile projects.